The differential collapse–filling evolution process of the paleo-underground river in the Northern Uplift of the Tarim Basin - Dong, Hong-Qi; Liang, Jia-Peng; Zhang, Qing-Yu; Li, Jing-Rui; Wan, Jun-Wei; Nie, Guo-Quan; Li, Yu-Lu (Frontiers in Earth Science, 2024)
The characteristics and stages of collapse-filling in paleo-underground rivers vary in recharge-runoff-discharge zones, constraining the associated fracture-caved reserviors in carbonate strata. This paper comprehensively utilizes core, fluid inclusion, and carbon-oxygen isotope to probe the evolution process and migration of collapse-filling in paleo-underground river in the Northern Uplift of Tarim Basin. The results show that: 1) More than three stages of collapse-filling were identified in recharge-runoff-discharge zones, and a four-stage differential collapse-filling process was proposed to summarize the evolution of paleo-underground river. 2) The collapse-filling process varies spatiotemporally in the recharge, runoff and discharge zones. Hydrodynamic strength and filling capacity migrate gradually from recharge zone to discharge zone. 3) Collapse-filling mechanisms, including gravity, suffusion and suction-erosion mechanisms, also vary along with the collapse-filling evolution process of paleo-underground river. The research provided a new insight to recognize and interpret the differential planar distribution and vertical filling of paleo-underground river system, which can be further applied to probe the fracture-caved karst reservoirs.